Pengaruh Kualitas Produk dan Promosi terhadap Keputusan Pembelian Sepatu New Balance di Kota Depok - Nurmaningsih Nurmaningsih; Rafiqa Maulidia; Novia Eka Nissrina (BADAN PENERBIT STIEPARI PRESS, 2025)
The increasingly competitive business environment demands that companies continuously innovate, particularly in meeting consumer needs for high-quality products. One of the popular footwear brands among young people is New Balance, known for its product quality and promotional strategies. A survey by APINDO shows that 60% of consumers in Depok consider product quality as the main factor in their purchasing decisions, while 40% are influenced by promotions. This study aims to determine the effect of Product Quality and Promotion on Purchase Decisions for New Balance shoes in Depok City. A quantitative method was employed, with data collected through questionnaires from 100 respondents. The data were analyzed using SPSS version 27, involving validity and reliability tests, classical assumption tests, regression analysis, and hypothesis testing. The findings show that Product Quality has a significant partial effect on Purchase Decisions, while Promotion does not. Simultaneously, both variables affect Purchase Decisions, with Product Quality being the most dominant factor. These results support APINDO’s findings and confirm that improving product quality is an effective strategy to influence consumer purchase decisions.